2010
DOI: 10.1002/jssc.200900861
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic cell grinder extraction of anthraquinones from Radix et Rhizoma Rhei and determination by ultra‐performance liquid chromatography

Abstract: An ultrasonic cell grinder extraction (UCGE) method has been developed and applied to extract five anthraquinones (physcion, chrysophanol, emodin, rhein, and aloe-emodin) from radix et rhizoma Rhei. Several parameters of UCGE procedure, including ultrasonic cell grinder running mode, type and volume of extraction solvent and extraction time, were optimized. The determination was preformed on a Waters ultra-performance LC BEH C(18) column using gradient elution system. A baseline separation could be achieved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…The main active compounds of rhubarb are thought to be anthraquinone derivatives, which include emodin, chrysophanol, aloe-emodin, rhein, and physcion. 5 Among them, physcion is found in the R. tanguticum , R. emodii , and fungus Microsporum sp., 7 9 and has been demonstrated to have anti-inflammatory, hepatoprotective, and anti-fungal activities. 8 , 10 13 It was also reported that physcion inhibited the growth of various human cancer cell lines, including HeLa (cervical cancer cells), A549 (lung cancer cells), HL-60 (leukemia cells), and SW680 (colon cancer cells).…”
Section: Introductionmentioning
confidence: 99%
“…The main active compounds of rhubarb are thought to be anthraquinone derivatives, which include emodin, chrysophanol, aloe-emodin, rhein, and physcion. 5 Among them, physcion is found in the R. tanguticum , R. emodii , and fungus Microsporum sp., 7 9 and has been demonstrated to have anti-inflammatory, hepatoprotective, and anti-fungal activities. 8 , 10 13 It was also reported that physcion inhibited the growth of various human cancer cell lines, including HeLa (cervical cancer cells), A549 (lung cancer cells), HL-60 (leukemia cells), and SW680 (colon cancer cells).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for such phenomenon could be due to the mechanics of synergistic effects of ultrasonic and microwave on the cell walls resulting in a significantly increased accessibility and extractability of the anthraquinones [14]. Compared to the previous studies, the extraction yields of five anthraquinones by IL-UMAE was much higher (28.00 mg g -1 ) than that of ultrasonic cell grinder extraction, maceration, ultrasonication, and CO 2 SFE (2.70, 2.31, 2.42, 0.33 mg g -1 , respectively) [12,30]. As extraction solvents, [bmim]Br solution and ethanol had similar results in the extraction of anthraquinones from rhubarb, which was similar to the previous studies [21].…”
Section: Comparison Of Different Extraction Techniquesmentioning
confidence: 55%
“…Stability was investigated using the extract of the sample solution that was stored at room temperature (about 25°C) and analyzed at 0, 6,12,18,24,30,36,42, 48 h, respectively. The RSDs of the contents of emodin, rhein, aloeemodin, physcion and chrysophanol were 1.5, 2.0, 1.8, 2.1 and 2.4%, respectively.…”
Section: Uplc Methods Validationmentioning
confidence: 99%
“…Ultrasound‐assisted extraction is a novel and improved strategy for edible fruits extraction (Zou et al ., ; Xu & Pan, ), which not only increases extraction efficiency but also minimises the consumption of unpleasant petroleum‐based solvents (Rostagno et al ., ; Zuo et al ., ; Wang et al ., ). Most recently, an ultrasonic cell grinder extraction (UCGE) method was reported as a green, inexpensive and easy‐to‐use method (Wang et al ., ; Li et al ., ). During the UCGE process, the ultrasonic energy is centralised in the top part of the probe and induces the cavitation of the extraction solvent.…”
Section: Introductionmentioning
confidence: 99%